ACID-MAKING FUNCTION OF STOMACH WITH CHRONIC GASTRITIS AND CHRONIC GASTRITIS WITH ACCOMPANYING PANCREAS AFFECTION - Скубицька, Л.Д.; Севериновська, О.В. (World of Medicine and Biology, 2015)
The dependence of the values of gastric juice acidity on the digestive function of the alimentary tract in the diseased with several pathologies – chronic gastritis and with accompanying pancreas affection – has been investigated. The decrease of acid production of the stomach in the diseased I (chronic gastritis) and the diseased II (chronic gastritis with pancreas affection) has been detected, with more noticeable effect in the group with accompanying pathology. The representatives of group II demonstrated more significant decrease in the functions of animal protein digestion, decomposition and assimilation of lipid food components and plant fiber digestion. It has been established that with chronic gastritis with the accompanying pancreas affection, the acid-making function of the stomach decreases and may cause not only complex pathological conditions, but also influence the digestive function of the alimentary tract as a whole.